Professional care networks of frail older people: an explorative survey study from the patient perspective - Grol, Sietske M.; Molleman, Gerard R. M.; Wensing, Michel; Kuijpers, Anne; Scholte, Joni K.; Muijsenbergh, Maria T. C. van den; Scherpbier, Nynke D.; Schers, Henk J. (International journal of integrated care, 2020)
Article: Professional Care Networks of Frail Older People: An Explorative Survey Study from the Patient Perspective
Gesehen am 20.04.2020